The Implementation of the Brain-based Learning Model in Elementary Schools Studied from a Literature Review - Oktaviani, Anna Maria; Gunardi, Ari; Supena, Asep (Teknodika, 2023)
This research is to find out how the learning process of the "brain-based learning" model at the elementary school level. In this case, neuropedagogy is an interdisciplinary approach combining neuroeducation, psychology, and education by developing innovative methods, curricula, skills, and initiatives to use findings in learning, memory, language, and other fields. Cognitive neuroscience further aims to provide educators with knowledge about the best teaching and learning strategies. This study thus used a literature review using a descriptive analysis method on brain-based learning methods/models, learning models suitable to be applied in elementary education. By knowing the child's development, the brain-based learning method or model will be appropriate for teaching elementary school pedagogy.